A Novel Intimate Partner Violence Curriculum for Internal Medicine Residents: Development, Implementation, and Evaluation - Insetta, Emily R. (MedEdPORTAL, 2020)
INTRODUCTION: Intimate partner violence (IPV) is a prevalent problem with profound health consequences. Research suggests that internal medicine (IM) residents are unprepared to screen for and address IPV. We designed a curriculum to improve IM residents’ knowledge, attitudes, and practices in caring for IPV survivors. METHODS: The curriculum was delivered to first-year IM residents from 2016 to 2017 at Johns Hopkins Bayview. Part 1 was 60 minutes long, with a video, evidence-based didactic teaching, and case-based discussion. Part 2 was 90 minutes long, with evidence-based didactic teaching, role-play of patient-provider conversations about IPV, and debriefing about strategies for discussing IPV. We evaluated knowledge, confidence, and self-reported behaviors pre- and postintervention using two-tailed paired t tests. RESULTS: Thirty-two residents received IPV training. In comparing precurriculum (n = 29, 91% of total participants) and postcurriculum (n = 28, 88% of total participants) surveys, there was significant improvement in knowledge about IPV (p < .001). Postcurriculum, learners reported greater confidence in detecting IPV (p < .001), documenting IPV (p < .001), and referring to resources (p < .001). Participants reported increased comfort with managing difficult emotions about IPV in patients (p < .01) and themselves (p < .001) and increased comfort in discussing IPV with female (p < .001) and male (p < .001) patients. Postcurriculum, all respondents felt they were more skillful in discussing IPV and would be more likely to screen for IPV. DISCUSSION: Our curriculum improved residents’ knowledge, confidence, comfort, and preparedness in screening for and discussing IPV.